Hard choices : critical years in America's foreign policy - Vance, Cyrus (Simon and Schuster, 1983)
Person, gripping, frank, this is the engrossing account by former Secretary of State Cyrus Vance of the hurly-burly of international affairs. With a candor few statesmen have matched, he talks about the four years, as head of the State Department, he was the chief U.S. spokesman for our foreign policy.